Quantitative analysis of segmented satellite network architectures: A maritime surveillance case study - Fraire, Juan Andres (2024)
This paper presents an in-depth trade-off analysis of a Swarm Satellite Constellation (SSC) Mission for Earth observation that leverages Segmented Architecture (SA), a concept designed by the Argentinian Space Agency (CONAE) within the New Space philosophy. This architecture consists of a scenario featuring a networked constellation of small, cooperative satellites to enhance mission flexibility, reliability, coverage, and cost-effectiveness. Despite its promising prospects, SA features challenges in its mission design and definition phases due to the complex interplay between distributed space systems, technological innovation, and geographical landscapes. Our study analyzes an innovative quantitative analysis framework integrated with Ansys´ Systems Toolkit (STK). The resulting software tool models critical components, including ground and space segments, orbital dynamics, coverage, onboard processing, and communication links. We focus on a hypothetical SARE mission to detect illicit maritime activity near Argentina´s Exclusive Economic Zone (EEZ). This case study constitutes an archetypal mission elucidating the architecture´s benefits and complexities, addressing swarm coverage, contact dynamics, and data handling strategies. Results contribute to discussions on the practical trade-off in current and future Segmented Satellite Architectures with multiple mission objectives.